2006
DOI: 10.2139/ssrn.905099
|View full text |Cite
|
Sign up to set email alerts
|

Aggregate Unemployment Decreases Individual Returns to Education

Abstract: Die Discussion Papers dienen einer möglichst schnellen Verbreitung von neueren Forschungsarbeiten des ZEW. Die Beiträge liegen in alleiniger Verantwortung der Autoren und stellen nicht notwendigerweise die Meinung des ZEW dar.Discussion Papers are intended to make results of ZEW research promptly available to other economists in order to encourage discussion and suggestions for revisions. The authors are solely responsible for the contents which do not necessarily represent the opinion of the ZEW.Download this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Relationship between returns to schooling and unemployment rate was studied for Germany by Ammermueller et al (2009). They found that an increase in regional unemployment by 1% decreased returns to education by 0.005 percentage points.…”
Section: Theoretical Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Relationship between returns to schooling and unemployment rate was studied for Germany by Ammermueller et al (2009). They found that an increase in regional unemployment by 1% decreased returns to education by 0.005 percentage points.…”
Section: Theoretical Settingmentioning
confidence: 99%
“…Unemployment rate at the local level is additionally included into the Mincer wage regression together with its interaction term with years of schooling to capture the impact that unemployment exerts on the wages and on the premium to additional year of schooling. The literature findings on how Evolution of private returns to schooling unemployment rate influences the returns to schooling are ambiguous (Ammermueller et al, 2009). Returns to education would decrease with unemployment rate if wages of high skilled were less sensitive to unemployment rate than the wages of low skilled.…”
Section: Theoretical Background and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Also, if unemployment increases and, as a consequence, job queues lengthen, employers may react by increasing hiring standards (including the required level of education). Similarly, Ammermueller et al (2009) also suggest that returns to education among skilled workers are less affected by the economic cycle than those of unskilled ones, and this is for two reasons. On the one hand, unskilled workers are more replaceable.…”
Section: Migrant-natives Differentials In Returns To Educationmentioning
confidence: 99%
“…The variable firm size, which is measured in terms of number of employees, has four categories: 1-9 (reference category), 10-49, 40-249 and 250+. Following Ammermueller et al (2009), a continuous variable capturing the logarithm of the regional unemployment rate has also been included. To construct this, each individual was assigned the annual average unemployment rate registered in his/ her region of residence, using the Labour Force Survey as the source.…”
Section: Data and Variablesmentioning
confidence: 99%